Afro Samurai - Surge (Firm). (Santa Clara, CA : Surge : Namco Bandai Games, 2009)
One Samurai roams the land with a mission of revenge. He will never know rest until his father's blood is vindicated.
Title from disc label.
1 player. Other features supported: Live online enabled, in-game Dolby digital.
System requirements: Xbox 360 with NTSC designation; 128 KB memory.
Keywords: Samurai; Hand-to-hand fighting; Revenge; African Americans; Video games